A Quest for Revenue and Tax Incidence in Uganda - Matovu, John.; Chen, Duanjie; Reinikka-Soininen, Ritva (Washington, D.C. : International Monetary Fund, 2001)
This paper examines tax policy and tax reforms in Uganda. Using household survey evidence, the paper identifies which taxes are progressive and investigates whether tax reforms have made the poor better or worse off. Household survey analysis reveals that some of the tax reforms implemented in the 1990s were generally pro-poor. The paper also examines business taxation and the actual tax burden on firms' capital investment. The analysis demonstrates that, even when the country's level of public revenue is low at the macroeconomic level, rapidly increasing taxation may pose a constraint to private investment at the microeconomic level.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet